Non-randomized therapy trial to determine the safety and efficacy of heavy ion radiotherapy in patients with non-resectable osteosarcoma - Blattmann, Claudia; Oertel, Susanne; Schulz-Ertner, Daniela; Rieken, Stefan; Haufe, Sabine; Ewerbeck, Volker; Unterberg, Andreas; Karapanagiotou-Schenkel, Irini; Combs, Stephanie; Nikoghosyan, Anna; Bischof, Marc; Jäkel, Oliver; et al. (BMC cancer, 2010)
Background - Osteosarcoma is the most common primary malignant bone tumor in children and adolescents. For effective treatment, local control of the tumor is absolutely critical, because the chances of long term survival are <10% and might effectively approach zero if a complete surgical resection of the tumor is not possible. Up to date there is no curative treatment protocol for patients with non-resectable osteosarcomas, who are excluded from current osteosarcoma trials, e.g. EURAMOS1. Local photon radiotherapy has previously been used in small series and in an uncontrolled, highly individualized fashion, which, however, documented that high dose radiotherapy can, in principle, be used to achieve local control. Generally the radiation dose that is necessary for a curative approach can hardly be achieved with conventional photon radiotherapy in patients with non-resectable tumors that are usually located near radiosensitive critical organs such as the brain, the spine or the pelvis. In these cases particle Radiotherapy (proton therapy (PT)/heavy ion therapy (HIT) may offer a promising new alternative. Moreover, compared with photons, heavy ion beams provide a higher physical selectivity because of their finite depth coverage in tissue. They achieve a higher relative biological effectiveness. Phase I/II dose escalation studies of HIT in adults with non-resectable bone and soft tissue sarcomas have already shown favorable results. - - Methods/Design - This is a monocenter, single-arm study for patients ≥ 6 years of age with non-resectable osteosarcoma. Desired target dose is 60-66 Cobalt Gray Equivalent (Gy E) with 45 Gy PT (proton therapy) and a carbon ion boost of 15-21 GyE. Weekly fractionation of 5-6 × 3 Gy E is used. PT/HIT will be administered exclusively at the Ion Radiotherapy Center in Heidelberg. Furthermore, FDG-PET imaging characteristics of non-resectable osteosarcoma before and after PT/HIT will be investigated prospectively. Systemic disease before and after PT/HIT is targeted by standard chemotherapy protocols and is not part of this trial. - - Discussion - The primary objectives of this trial are the determination of feasibility and toxicity of HIT. Secondary objectives are tumor response, disease free survival and overall survival. The aim is to improve outcome for patients with non-resectable osteosarcoma. - - Trail Registration - Registration number (ClinicalTrials.gov): NCT01005043
Gesehen am 15.02.2023